Zinc Promotes Osteoblast Differentiation in Human Mesenchymal Stem Cells Via Activation of the cAMP-PKA-CREB Signaling Pathway - Park, Kwang Hwan; Choi, Yoorim; Yoon, Dong Suk; Lee, Kyoung-Mi; Kim, Dohyun; Lee, Jin Woo (Stem cells and development, 2018)
The crucial trace element zinc stimulates osteogenesis in vitro and in vivo. However, the pathways mediating these effects remain poorly understood. This study aimed to investigate the effects of zinc on osteoblast differentiation in human bone marrow-derived mesenchymal stem cells (hBMSCs) and to identify the molecular mechanisms of these effects. In hBMSCs, zinc exposure resulted in a dose-dependent increase in osteogenesis and increased mRNA and protein levels of the master transcriptional factor RUNX2. Analyzing the upstream signaling pathways of RUNX2, we found that protein kinase A (PKA) signaling inhibition blocked zinc-induced osteogenic effects. Zinc exposure increased transcriptional activity and protein levels of phospho-CREB and enhanced translocation of phospho-CREB into the nucleus. These effects were reversed by H-89, a potent inhibitor of PKA. Moreover, zinc exposure led to dose-dependent increases in levels of intracellular cyclic adenosine monophosphate (cAMP). These findings indicate that zinc activates the PKA signaling pathway by triggering an increase in intracellular cAMP, leading to enhanced osteogenic differentiation in hBMSCs. Our results suggest that zinc exerts osteogenic effects in hBMSCs by activation of RUNX2 via the cAMP-PKA-CREB signaling pathway. Zinc supplementation may offer a promise as a potential pharmaceutical therapy for osteoporosis and other bone loss conditions.